Somatotype and body image as predictors of overall and abdominal obesity in college students from northern Mexico - Ramos-Jimenez, Arnulfo (2018)
Objective: To maximize somatotype and body image (BI) as predictors of overweight/obesity and abdominal obesity in university students in northern Mexico. Methods: Body mass index (BMI, kg/m2), waist circumference (WC, cm), somatotype and self-perception of the BI from 329 college students (17-35 years, 51% males) were evaluated; Sensitivity, specificity, precision and accuracy of said variables were also evaluated, using ROC curves and classification/regression tree analysis. Results: Average BMI and WC were 24 ± 4 and 79 ± 9 (male) and 25 ± 5 and 81 ± 10 (female). Somatotype and BI changes predicted both BMI (≥ 82.6%) and WC (≥ 87.4%); A somatotype scale ≥ 5.35 (endomorphy), ≥ 4.75 (mesomorphy) and ≤ 1.25 (ectomorphy), or an BI> 3.5 predicted overweight/obesity, while a somatotype ≥ 6.55 (endomorphy), ≥ 5.45 (mesomorphy), ≤ 1.15 (ectomorphy), or a BI ≥ 4.5 predicted abdominal obesity and thinness idealization.